Feto-maternal outcome of pregnancies diagnosed as hypothyroidism after 28 weeks of gestation, at a tertiary hospital - Garg, Asha; Goyal, Sham Sunder; Bedi, Mini; ., Muskan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The most frequent thyroid alteration observed in pregnancy is hypothyroidism with subclinical hypothyroidism being more common than overt hypothyroidism. Women with thyroid dysfunction both overt and subclinical are at increased risk of pregnancy-related complications. In present study we assessed feto-maternal outcome of pregnancies in whom hypothyroidism was diagnosed after 28 weeks of gestation. Methods: This study was conducted in the department of obstetrics and gynaecology, Adesh institute of medical sciences and research Medical College, Bathinda. The present study was of prospective, observational design, conducted in pregnant women with more than 28 weeks pregnancy, first time diagnosed as hypothyroid (TSH>3.0 mIU/l). Results: In present study total 37 patients completed study protocol, 6 patients were delivered at other hospital. Most patients were less than 20 years (32%), nulliparous (68%). 19% patients delivered preterm either due to spontaneous labour or labour induction for obstetric reason. 62% patients delivered vaginally, 35% underwent LSCS. In present study maternal complications such as preterm labour (24%), hypertensive disorders of pregnancy (22%), oligohydramnios (16%), overt/gestational diabetes mellitus (8%) and post-partum haemorrhage (5%) were noted. 2.5-3.4 kg birth weight was most common group (65%). Total 16 % babies required neonatal resuscitation. Babies requiring neonatal resuscitation were admitted in NICU for observation and for any further management. Neonatal jaundice was noted in 30% babies. Total 22% babies needed NICU admission. We noted early neonatal death in one baby. No maternal mortality was noted. Conclusions: Treatment of maternal hypothyroidism is essential, because adverse outcomes for both mother and baby are greatly reduced, if not eliminated, when patients are treated.